(untitled) (American Journal of Interdisciplinary Research and Development, 2024)
Working with folklore groups involves collaborating with communities to protect and promote their cultural heritage. This research paper explores collaborative methodologies and the importance of preserving folklore traditions. Following the IMRAD format, this study examines the impact of community participation, documentation methods, and digital preservation strategies in supporting folklore groups.